2022
DOI: 10.1038/s41598-022-11735-2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and associated factors among mature and older adults living in the community of Gondar town, Ethiopia, 2020

Abstract: Cognitive impairment and dementia are age-related major public health concerns in the elderly population. It is a major cause of disability, dependency, and poor quality of life. However, in Ethiopia, the magnitude of this cognitive impairment among the elderly community was not investigated. Hence, this study sought to determine the prevalence of cognitive impairment and associated factors among mature and older adults living in the community of Gondar town, Ethiopia, in 2020. A community-based cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
3
6
1
2
Order By: Relevance
“…We found that CI (in any form) had a prevalence of 91.7%, with 28.6% of participants exhibiting severe CI. Our study found a higher prevalence of CI compared to studies conducted elsewhere, which reported a prevalence ranging from 4.5% to 71.9% [15][16][17][18][19][20][21][22][23]. The higher prevalence in our study can be ascribed to the study group's profile, with all participants ≥65 years of age, ranging from 65 to 95 years.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…We found that CI (in any form) had a prevalence of 91.7%, with 28.6% of participants exhibiting severe CI. Our study found a higher prevalence of CI compared to studies conducted elsewhere, which reported a prevalence ranging from 4.5% to 71.9% [15][16][17][18][19][20][21][22][23]. The higher prevalence in our study can be ascribed to the study group's profile, with all participants ≥65 years of age, ranging from 65 to 95 years.…”
Section: Discussioncontrasting
confidence: 60%
“…Illiteracy and depression were positively associated with higher forms of CI, whereas living in urban areas, living with spouses, and not consuming alcohol were found to be negatively associated with higher forms of CI. Illiteracy has been reported as an important risk factor associated with CI in studies conducted in multiple settings across the world [15][16][17]20,21,24,25]. The plausibility of illiteracy as a risk factor for CI can be explained by the fact that education is an important aspect of cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…According to the published document from the ministry, the estimated prevalence of dementia in Ethiopia is highly under estimated at 2.4% (15). Contrary to this, Gela et al (16), reported out of 403 older individuals screened for cognitive impairment, 43.8% of them fulfilled criteria for cognitive impairment. The authors further reported, being older age, unable to read and write, female gender, low income, poor social support, and rural dwelling were an independent predictor of cognitive impairment.…”
Section: Introductionmentioning
confidence: 81%
“…The CNHS included 6233 participants aged ≥ 15 years and used a stratified and multistage selection of participants. In our study, we eliminated participants between 15 and 59 years of age (n = 4202) due to: (1) difference of prevalence of objective cognitive function compared with people aged ≥ 60 years; (2) CI being a major public health concern in the elderly population; (3) I being a major cause of disability, dependency, and poor quality of life [ 21 ]. Participants with missing data on cardiovascular risk factors and CI were eliminated (n = 770).…”
Section: Methodsmentioning
confidence: 99%